Consolidation of calcium phosphate powder through microwave sintering / Natasha Ahmad Nawawi, Ramesh Singh and Tan Chou Yong - Ahmad Nawawi, Natasha; Singh, Ramesh; Tan, Chou Yong (Universiti Teknologi MARA Cawangan Pulau Pinang, 2018)
In the last 50 years, the major drawback of HA ceramic usage in clinical applications is its inherent brittleness and lower mechanical strength than those of cortical bone. This is turn calls for the development of dense nanostructured HA with the major concern is to enhance densification while limiting its grain growth. Hence, a promising way to obtain this could be a fabrication of fully dense nanostructured materials through sintering process. In this work, eggshell derived hydroxyapatite (HA-Es) powder has been prepared via solid state sintering and its sinterability was investigated through microwave sintering at various sintering temperatures (950-1250 °C). The phase stability, microstructural evolution and relative density of HA-Es were deliberated. The results indicate that microwave sintering regime has been successfully employed and this short sintering regime did not promote extensive grain growth even when sintered at high temperature.